The Influencesof Investment Policy, Profitability, And Capital Structurecon Firm Value In The Energy Sectorslisted Onxthe Indonesia Stock Exchange (IDX) - Windi Rika Julitia; Joko Susilo; Yasir Hudzaifah (UNIVED Press, 2025)
This study aims to analyze and assess the impact of capital structure, profitability, and investment policy on firm value in the energy sector, focusing on firms that were publicly listed on the Indonesia Stock Exchange (IDX) between 2021 and 2024. Using a documentation method and a quantitative approach, the data is derived from the annual financial statements of energy companies officially published on the IDX website (www.idx.co.id). Following the Chow, Hausman, and Lagrange Multiplier tests to determine the most appropriate model, Panel regression model with the Common Effects Model was employed as the analytical method. The findings indicate that while capital structure does not have a significant partial effect, both profitability and investment policy exert a positive*and*significant influence on firm value. However, when assessed simultaneously, all three independent variables significantly affect firm value. The adjusted*R-squared value of 97.58% suggests that the model effectively explains the dependent variable. These findings imply that corporate management should prioritize improving profitability efficiency and implementing targeted investment strategies, as both are key factors in enhancing long-term firm value and attracting investor interest.